Exploring Teachers' and Students’ Attitudes towards English Language Large Classes at Herat University, Afghanistan - Ahmad Fawad Kakar; Kawita Sarwari (Journal of Foreign Language Teaching and Learning, 2022)
This study is qualitative research that seeks to investigate the large class teaching challenges and the instructors' coping strategies through the perspectives of five English language instructors of the English Department of Herat University. Furthermore, the perspectives of ten juniors and seniors of the English Department of Herat University on large EFL classes are also explored. The data collected through face-to-face semi-structured interviews were analyzed thematically. In other words, the data were divided into major and sub-themes, considering the study’s theoretical framework-Kumaravadevelu’s post-method pedagogy- and the research questions. The findings indicated that challenges, such as multi-level students, under-resourced context, a large number of students, giving feedback, assessing students, classroom management, and students' engagement, are the challenges behind large classes in Afghanistan. Further, reducing the number of students, providing teachers with capacity-building programs and teaching resources are also discussed.